2023
DOI: 10.17343/sdutfd.1181696
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Factors Associated With Fear of Hypoglycemia and Perception of Self-Efficacy in Diabetes Patients Using Insulin

Abstract: Amaç: Bu çalışmanın amacı insülin kullanan diyabetli hastalarda hipoglisemi korkusu ve öz-yeterlilik algısı ile ilişkili faktörleri belirlemektir. Gereç ve Yöntem: Tanımlayıcı ve ilişki arayıcı tipteki bu araştırma Aralık 2016-Şubat 2017 tarihleri arasında bir Devlet Hastanesi’nde diyabet eğitim hemşiresi tarafından takip edilen toplam 136 hasta ile yapılmıştır. Verilerin toplanmasında literatür doğrultusunda hazırlanan “Hasta Tanıtım Formu”, “Çok Boyutlu Diyabet Anketi’nin Öz-yeterl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In our quantitative data, it was seen that the hypoglycaemic confidence level scores of those who went to regular doctor check-ups were higher, although not significantly. In a study, it was reported that patients who regularly have health check-ups experience less fear of hypoglycaemia due to higher disease management (Özkaptan & Demirci, 2023). Polonsky et al (2015) reported that patients with good glycemic control had high hypoglycaemic confidence.…”
Section: Theme 3: Managing Hypoglycaemiamentioning
confidence: 99%
“…In our quantitative data, it was seen that the hypoglycaemic confidence level scores of those who went to regular doctor check-ups were higher, although not significantly. In a study, it was reported that patients who regularly have health check-ups experience less fear of hypoglycaemia due to higher disease management (Özkaptan & Demirci, 2023). Polonsky et al (2015) reported that patients with good glycemic control had high hypoglycaemic confidence.…”
Section: Theme 3: Managing Hypoglycaemiamentioning
confidence: 99%